Design and characterization of a new bioreactor for continuous ultra-slow uniaxial distraction of a three-dimensional scaffold-free stem cell culture - Weiss, Stefan; Henle, Philipp; Roth, Wolfgang; Bock, Rosalie; Boeuf, Stephane; Richter, Wiltrud (Biotechnology progress, 2011)
A computer controlled dynamic bioreactor for continuous ultra-slow uniaxial distraction of a scaffold-free three-dimensional (3D) mesenchymal stem cell pellet culture was designed to investigate the influence of stepless tensile strain on behavior of distinct primary cells like osteoblasts, chondroblasts, or stem cells without the influence of an artificial culture matrix. The main advantages of this device include the following capabilities: (1) Application of uniaxial ultra-slow stepless distraction within a range of 0.5-250 μm/h and real-time control of the distraction distance with high accuracy (mean error −3.4%); (2) tension strain can be applied on a 3D cell culture within a standard CO2-incubator without use of an artificial culture matrix; (3) possibility of histological investigation without loss of distraction; (4) feasibility of molecular analysis on RNA and protein level. This is the first report on a distraction device capable of applying continuous tensile strain to a scaffold-free 3D cell culture within physiological ranges of motion comparable to distraction ostegenesis in vivo. We expect the newly designed microdistraction device to increase our understanding on the regulatory mechanisms of mechanical strains on the metabolism of stem cells. © 2010 American Institute of Chemical Engineers Biotechnol. Prog., 2011
Online veröffentlicht November 9, 2010
Gesehen am 18.11.2022